Water balance variability in the confined Aba'ala limestone graben at the western margin of the Danakil depression, northern Ethiopia. Issue 6 (26th April 2018) - Meaza, Hailemariam; Frankl, Amaury; Poesen, Jean; Zenebe, Amanuel; Van Eetvelde, Veerle; Demissie, Biadgilgn; Asfaha, Tesfaalem Ghebreyohannes; Deckers, Jozef; Raes, Dirk; Nyssen, Jan
ABSTRACT: Marginal grabens are major development corridors in Ethiopia, and need to be understood for proper assessment of the hydrological budget. This study investigates the water balance of the Aba'ala graben (553 km 2 ) in the period 2015–2016 under the challenge of data scarcity. We measured the rainfall and river discharge in order to analyse the runoff components of the graben. The rainfall volume in the Aba'ala graben showed erratic behaviour, which led to rapid flood runoff of the major river into the graben bottom. The average annual inflow and outflow of the graben bottom for the period 2015–2016 amounted to 364 and 254 hm 3, respectively. However, flood runoff and evapotranspiration had a marked effect on water availability. Water storage took 36% of the water inflow into the graben bottom. Sustainable water management could reduce the temporal variation of the water storage in Aba'ala graben.